2002
DOI: 10.1128/jvi.76.22.11236-11244.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mandelic Acid Condensation Polymer: Novel Candidate Microbicide for Prevention of Human Immunodeficiency Virus and Herpes Simplex Virus Entry

Abstract: Presently marketed vaginal barrier methods are cytotoxic and damaging to the vaginal epithelium and natural vaginal flora when used frequently. Novel noncytotoxic agents are needed to protect men and women from sexually transmitted diseases. One novel candidate is a mandelic acid condensation polymer, designated SAMMA. The spectrum and mechanism of antiviral activity were explored using clinical isolates and laboratory-adapted strains of human immunodeficiency virus (HIV) and herpes simplex virus (HSV). SAMMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 41 publications
6
81
1
Order By: Relevance
“…Little antiviral activity was observed when the target T cells were treated with PPCM and then washed to remove drug prior to viral exposure, suggesting that the drug needs to be present at the time of viral exposure. These data are consistent with earlier studies indi- cating that the drug primarily targets the virus and has greater antiviral activity against X4 than against R5 viruses (21).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Little antiviral activity was observed when the target T cells were treated with PPCM and then washed to remove drug prior to viral exposure, suggesting that the drug needs to be present at the time of viral exposure. These data are consistent with earlier studies indi- cating that the drug primarily targets the virus and has greater antiviral activity against X4 than against R5 viruses (21).…”
Section: Resultssupporting
confidence: 82%
“…Prior studies have demonstrated that PPCM inhibits HSV infection primarily by binding to the viral envelope and inhibiting viral binding and entry (21). We have extended these in vitro observations and demonstrated that PPCM also blocks HSV infection of cervical explant cultures (Fig.…”
Section: Vol 82 2008 Ppcm Blocks Hiv and Prevents Genital Hsv 6579supporting
confidence: 57%
See 1 more Smart Citation
“…HSV-2 recombinant glycoprotein B (gB2) was generated using the Bac-to-Bac system (Gibco) and purified by heparin-affinity chromatography. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by silver staining confirmed its purity (25). Anti-gB2 monoclonal antibody (1123) was purchased from the Goodwin Institute, Plantation, Fla.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that rabbit ␣ defensin NP-1 blocks HSV-2 infection at a step postbinding, but similar studies with human ␣ defensins have not been reported. To define the step(s) in HSV invasion that was blocked by retrocyclin 2 and HNPs 1 to 3 (25), kinetic assays were performed as previously described. CaSki cells were cooled to 4°C and exposed to virus for 3 h to allow viral attachment.…”
Section: Vol 78 2004 Defensins Protect Cells From Hsv Infection 5149mentioning
confidence: 99%